2011
DOI: 10.1136/annrheumdis-2011-200096
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 34 expression is associated with synovitis severity in rheumatoid arthritis patients

Abstract: This work for the first time identifies IL-34 expression in the synovial tissue of patients with arthritis. This cytokine, as a downstream effector of TNFα and IL-1β, may contribute to inflammation and bone erosions in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
136
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 17 publications
6
136
0
Order By: Relevance
“…The pro-inflammatory cytokines TNF-α and IL-1β regulate IL-34 expression in synovial and gingival fibroblasts by a mechanism involving NF-κB and MAPK 5,8) . Martinez 21) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pro-inflammatory cytokines TNF-α and IL-1β regulate IL-34 expression in synovial and gingival fibroblasts by a mechanism involving NF-κB and MAPK 5,8) . Martinez 21) .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that IL-34 plays a role in inflammation, as it increases IL-6 and chemokine levels in human whole blood 11) . Interleukin-34 is also expressed in rheumatoid arthritis (RA) synovium, where it has been shown to be associated with severity of synovitis, and is elevated in serum and synovial fluid from RA patients 8) . Furthermore, IL-34 is produced by synovial and gingival fibroblasts in response to TNF-α and IL-1β through the NF-κB and c-Jun N-terminal kinase (JNK) pathways 5,8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since pro-inflammatory cytokines such as IL-1β and TNF-α play a crucial role in RA and since we previously demonstrated that TNF-α induces IL-34 expression, 5 we studied the effect of TGF-β1 and BMP-2 in inflammatory conditions. To this end, cells were treated with TNF-α.…”
Section: Tgf-β1 Inhibits Il-34 Expression In Inflammatory Conditionsmentioning
confidence: 99%
“…Its expression, correlated with inflammation, the number of leucocytes and the severity of the synovitis, is upregulated by TNFα and IL-1β. 5 TGF-βs and BMPs, are proteins involved in control of many biological processes such as cell proliferation and differentiation. The importance of TGF-β for the pathogenesis of arthritis is emphasized by several observations made in patients and in animal models.…”
Section: Introductionmentioning
confidence: 99%